IDEALITAS DAN DESAIN PENGEMBANGAN BAHAN AJAR BAHASA ARAB - Muh Sabilar Rosyad (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2020)
Abstrac: This study aims to discuss the ideal Arabic language development design with a focus point on the understanding of teaching materials and their position in learning, the principles / foundations for the development of Arabic teaching materials, and the characteristics of Arabic teaching materials. Based on the above topic, this research uses descriptive analysis method with the type of library research. The conclusions resulting from him are: 1. Teaching materials are a set of subject matter or substance arranged coherently and systematically and displaying a complete figure of the competencies that students will master in learning activities. 2. The principles that must be considered in the development of Arabic are socio-cultural, psychological, linguistic and educational or teaching principles. 3. The ideal characteristics that must be present in teaching materials are: types of subjects, topics / discussion titles, supporting media (images / designs that can help students understand the meaning of related vocabulary), new vocabulary, text / learning material (found in student books and teacher), questions and exercises, enrichment of Arabic rules, games (if possible). 4. The design of the development of Arabic teaching materials can be done through the following steps: analysis, design, writing and preparation of materials, evaluation and revision.Keywords: Arabic language, development design, teaching materials.